Noise suppression of infrared thermal imaging of rocket exhaust plume using SPOD - Fu, Debin; Sun, Ao; Niu, Qinglin (Frontiers in Physics, 2024)
The environmental noise have a negative influence on the quality of infrared thermal imaging of the rocket exhaust plume. In this study, the noise data of the unsteady rocket exhaust plume flow field was simulated using Gaussian white noise, and the infrared thermal image of the plume was numerically calculated using the narrow band method (SNB) and the line of sight (LOS) method. The denoising of infrared thermal imaging was achieved through the spectral proper orthogonal decomposition (SPOD) inversion method. Results indicate that Gaussian white noise leads to larger infrared thermal image residuals in the intrinsic core of the plume compared to the mixed regions. The infrared thermal image in the 2.7 μm band is greatly affected by the noise with an average error of 21.1%, and the average error in the 4.3 μm band is 17.6%. After SPOD denoising, the error of the plume infrared thermal image is reduced by more than 50%.